Short‐T2 imaging for quantifying concentration of sodium (23Na) of bi‐exponential T2 relaxation. Issue 1 (30th July 2014) - Qian, Yongxian; Panigrahy, Ashok; Laymon, Charles M.; Lee, Vincent K.; Drappatz, Jan; Lieberman, Frank S.; Boada, Fernando E.; Mountz, James M.
<x xml:space="preserve">Abstract</x> Purpose This work intends to demonstrate a new method for quantifying concentration of sodium (23Na) of bi‐exponential T2 relaxation in patients on MRI scanners at 3.0 Tesla. Theory and Methods Two single‐quantum (SQ) sodium images acquired at very‐short and short echo times (TE = 0.5 and 5.0 ms) are subtracted to produce an image of the short‐T2 component of the bi‐exponential (or bound) sodium. An integrated calibration on the SQ and short‐T2 images quantifies both total and bound sodium concentrations. Numerical models were used to evaluate signal response of the proposed method to the short‐T2 components. MRI scans on agar phantoms and brain tumor patients were performed to assess accuracy and performance of the proposed method, in comparison with a conventional method of triple‐quantum filtering. Results A good linear relation (R2 = 0.98) was attained between the short‐T2 image intensity and concentration of bound sodium. A reduced total scan time of 22 min was achieved under the SAR restriction for human studies in quantifying both total and bound sodium concentrations. Conclusion The proposed method is feasible for quantifying bound sodium concentration in routine clinical settings at 3.0 Tesla. Magn Reson Med 74:162–174, 2015. © 2014 Wiley Periodicals, Inc.